A New Graphical User Interface Generator for Economic Models and its Comparison to Existing Approaches - Wolfgang Britz (German Journal of Agricultural Economics (GJAE), 2014)
The paper discusses the role of Graphical User Inter-faces in economic modelling and specifically the de-velopment of a new Graphical User Interface Genera-tor for applications realized in GAMS (General Alge-braic Modelling System), a widely used Algebraic Modelling Language for (bio-)economic simulation models. It motivates the development of GGIG (Gams Graphical Interface Generator) by reviewing existing approaches. In opposite to frameworks available for environmental and Agent Based Modelling, GUI ge-nerators for more classical economic models seem to be scarce. GGIG aims at a fast development process not requiring programming skills where simple user operable controls are defined in an XML file such that GAMS based projects can add easily a GUI. It com-prises quite versatile exploitation tools for interactive reporting (tables, graphs and maps) including a ma-chine learning package plus useful utilities, e.g. to generate a HTML based GAMS code documentation or batch execution. In opposite to other approaches, GGIG strictly separates the GUI and GAMS code, but does not offer IDE functionality. Applications to CAPRI, a rather complex model, and some smaller projects seem to show that researchers without formal programming training are able to develop and modify a GUI for their models, while model users can be quickly trained in GGIG based GUIs.
Keywords: 330